2022
DOI: 10.3390/ijerph19127083
|View full text |Cite
|
Sign up to set email alerts
|

Motor Functioning and Intelligence Quotient in Paediatric Survivors of a Fossa Posterior Tumor Following a Multidisciplinary Rehabilitation Program

Abstract: Background: Short- and long-term consequences after treatment for childhood fossa posterior tumors are extensively reported in the literature; however, papers highlighting physical function throughout rehabilitation and its correlation with Intelligence Quotient (IQ) are sparse. This study aims to describe the physical functioning and IQ of these survivors, their progression during rehabilitation, and the association with histopathological tumor classification. Additionally, the correlation between gross motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Our study, conducted on a fairly large sample of participants, confirms the results of other studies based on smaller samples showing that children who have survived cancer have cognitive and motor deficits [ 14 , 16 ]. Meanwhile, the large and varied clinical sample both in terms of the cancer survivor group and the control group could provide the solid rationale for improving and updating rehabilitation procedures aiming at restoring the neurocognitive and fine motor skills and potentially choosing the best pipeline for each individual patient, thus leading to potential improvements in cognitive outcomes and quality of life.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study, conducted on a fairly large sample of participants, confirms the results of other studies based on smaller samples showing that children who have survived cancer have cognitive and motor deficits [ 14 , 16 ]. Meanwhile, the large and varied clinical sample both in terms of the cancer survivor group and the control group could provide the solid rationale for improving and updating rehabilitation procedures aiming at restoring the neurocognitive and fine motor skills and potentially choosing the best pipeline for each individual patient, thus leading to potential improvements in cognitive outcomes and quality of life.…”
Section: Discussionsupporting
confidence: 89%
“…Pediatric brain tumors and childhood tumors of hematopoietic and lymphoid tissues account for the lion’s share of all pediatric cancer (leukemias, at 34%, and lymphomas, at 12%) [ 13 ]. A lot of research has demonstrated negative outcomes for pediatric brain cancer survivors, among which a decrease in cognitive, visual-motor, and visuospatial functioning were the most common [ 14 ]. This might be related to several factors: location of tumor as well as tumor origin and progression, type of therapy (for instance resection of a part of the brain for the pediatric cancer of the central nervous system), chemotherapy and radiation therapy, the consequences of treatment and hospitalization, age and time of the diagnosis, duration of treatment, and many other factors [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent study by Decock et al, among youth with PF tumors ( N = 56), motor performance deficits at the beginning of rehabilitation ranged from 5.35% (upper limb mobility) to 26.78% (balance). At the end of the rehabilitation, the prevalence of motor performance deficits ranged from zero percent (upper limb mobility) to 8.92% (balance) ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent study by Decock et al, among children with posterior fossa tumors (N = 56), motor performance de cits at the beginning of rehabilitation ranged from 5.35% (upper limb mobility) to 26.78% (balance). At the end of the rehabilitation, the prevalence of motor performance de cits ranged from zero percent (upper limb mobility) to 8.92% (balance) (20).…”
Section: Introductionmentioning
confidence: 99%